Assessment of Mental Workload among Consumer Packaging Operators in Palm Oil Mills using NASA-TLX - Rishelin, Nadya; Elviana, Rahmi; Zahrina, Nadhilah; Putri, Gustiarini Rika; Sari, Annisa Rahma (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The palm oil industry plays a vital role in the national economy through palm oil mills (POMs) that process fresh fruit bunches into crude palm oil and packaged products. The Consumer Packaging (CPC) department ensures product quality, yet its tasks requiring high accuracy, speed, and consistency may cause mental workload. This study assesses and analyzes the mental workload of Consumer Packaging (CPC) operators in a palm oil mill using the NASA-TLX method, involving eight respondents from the forklift, Samarpan machine, packing, and stuffing units. The results indicate an average NASA-TLX score of 82% (very high category), with effort identified as the dominant dimension (26%). Simulation of additional workers reduced workload to 59.6%. These findings highlight the importance of task redistribution, workplace improvements, and temporary contract workers to maintain productivity and operational sustainability.